2014
DOI: 10.1080/13102818.2014.901672
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Albanian goat breeds revealed by mtDNA sequence variation

Abstract: Albanian farmers have a long tradition in goat farming. Recently, several studies were carried out to determine genetic diversity of local goat populations, using molecular markers such as SNP (Single Nucleotide Polymorphisms), microsatellites and AFLP (Amplified Fragment Length Polymorphism). In the present study 77 mtDNA D-loop sequences from six different goat breeds were analysed. The results revealed 67 different haplotypes, with haplotype diversity ranging from 0.864 to 1 and nucleotide diversity values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This could be due to the fact that both the Indian and Chinese goat breeds are from the same lineage A (Joshi et al 2004, Liu et al 2006, Kamalakannan et al 2018. Study done in European goat breeds by Hoda et al (2014) indicated that in 6 Albanian goats, the average nucleotide diversity was 0.036 and average haplotype diversity was 0.996. Similar findings were also reported by Sardina et al (2006) in three Sicilian goat breeds with nucleotide diversity of 0.024 and haplotype diversity of 0.969.…”
Section: )mentioning
confidence: 99%
“…This could be due to the fact that both the Indian and Chinese goat breeds are from the same lineage A (Joshi et al 2004, Liu et al 2006, Kamalakannan et al 2018. Study done in European goat breeds by Hoda et al (2014) indicated that in 6 Albanian goats, the average nucleotide diversity was 0.036 and average haplotype diversity was 0.996. Similar findings were also reported by Sardina et al (2006) in three Sicilian goat breeds with nucleotide diversity of 0.024 and haplotype diversity of 0.969.…”
Section: )mentioning
confidence: 99%
“…Hasi goat is recognized as an endemic breed (Dobi et al, 2006). Based on the results of this study and results of previous studies on AFLP (Hoda et al, 2014) The phenotypic differentiation is based on traditional selection criteria applied by farmers. Even nowadays they continue to select goat kids for replacement based on: "Reddish color, medium size pending ears, and backward curled horns, high milk productive mothers with good developed teats, as well as the ability to browse high branches" (Dobi et al, 2016).…”
Section: The Place and The Local Resourcesmentioning
confidence: 99%
“…Goat biodiversity of different populations is described using qualitative and quantitative traits (Kume et al, 2012), or based on the visible profile (Bozgo et al, 2012). Genetic diversity of six local goat breeds is estimated previously by the use of different markers such as microsatellites (Hoda, Hyka, et al, 2011), AFLP (Hoda et al, 2012), mtDNA (Hoda et al, 2014) in the frame of Econogene project. The present study is focused on three local goat breeds: Dragobia, Velipoja and Smokthina.…”
Section: Introductionmentioning
confidence: 99%